Simulation of bone-determined range of motion in proximal humeral fractures. - Majed,A; Thangarajah,T; Krekel,P; Nelissen,R; Reilly,P; Bull,A; Emery,R (Shoulder Elbow, 2018)
Background: Predicting the outcome following fractures of the proximal humerus is an important consideration when effectively counselling patients and planning treatment. The purpose of the present study was to analyze different proximal humeral fracture configurations, using a computerized simulation model, aiming to predict the range of motion (ROM). Methods: The computer tomography scans of 79 proximal humeral fractures were analyzed using a customized software system that simulated the range of movement at the glenohumeral joint. Four fracture patterns were investigated: (1) head split fractures; (2) greater tuberosity fractures; (3) lesser tuberosity fractures; and (4) combined tuberosity fractures. Results: Intra-articular fractures had the smallest mean (SE) range of abduction and forward flexion [34.3° (6.6°) and 60.7° (12.4°)]. Isolated displaced greater tuberosity resulted in limited abduction but not forward flexion [75.0° (5.9°) and 118.2° (4.9°)]. Isolated lesser tuberosity fractures displayed a ROM comparable to that of healthy subjects [89.3° (3.3°) and 122.6° (3.4°) versus 102.3° (2.8°) and 96.2° (3.8°)]. The reduced head inclination angle was a relatively strong predictor of a limited range of abduction for all fracture types. Conclusions: The present study describes a novel simulation system used to quantify the bone-determined ROM in proximal humeral fractures and may be a useful adjunct in the diagnostic armamentarium for proximal humeral fractures.